Synthesis and Biological Activities of some Mixed - Cicdiamine Complexes of PT (II) Containing Piperine and Other Amines - Vu, Duong Ba; Da, Tran Thi; Dinh, Nguyen Huu (VNU Journal of Science: Natural Sciences and Technology; Vol 18 No 1, 2002)
Abstract